2020
DOI: 10.1097/aog.0000000000003864
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian Cancer After Prophylactic Salpingectomy in a Patient With Germline BRCA1 Mutation

Abstract: BACKGROUND: Women with germline BRCA1 or BRCA2 mutations have a lifetime risk of ovarian cancer of up to 46%. Opportunistic salpingectomy has been advocated as a risk-reducing strategy owing to increasing recognition of tubal origin, yet evidence of efficacy in this high-risk population is limited. CASE: This is the case of a woman with a BRCA1 mutation who underwent prophylactic mastectomy and bilateral salpingectomy with ovarian retention before the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…One of the ongoing studies recently published the effects of salpingectomy vs. RRSO on quality of life and demonstrated that QoL was better in the salpingectomy group than in the RRSO group [ 61 ]. However, it is known that new ovarian neoplasms can develop not only after salpingectomy but also after RRSO [ 62 , 63 ]. Looking at the ongoing studies, the efficacy analysis in risk reduction is a long-term balance, with the end dates of the ongoing studies planned beyond 2030 [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the ongoing studies recently published the effects of salpingectomy vs. RRSO on quality of life and demonstrated that QoL was better in the salpingectomy group than in the RRSO group [ 61 ]. However, it is known that new ovarian neoplasms can develop not only after salpingectomy but also after RRSO [ 62 , 63 ]. Looking at the ongoing studies, the efficacy analysis in risk reduction is a long-term balance, with the end dates of the ongoing studies planned beyond 2030 [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is known that new ovarian neoplasms can develop not only after salpingectomy but also after RRSO [ 62 , 63 ]. Looking at the ongoing studies, the efficacy analysis in risk reduction is a long-term balance, with the end dates of the ongoing studies planned beyond 2030 [ 62 , 63 ]. Meanwhile, only limited data on cancer risk reduction in this group of high-risk women are currently available [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, caution is needed with translating the tubal hypothesis into clinical practice before it is proven. 24 Besides, even if fallopian tubes are removed, initiated cells may spread to the ovary at a very early point. 20,22 The preferred left side has never been reported for OC origin in BRCA mutation carriers, herein verified for both ovary and tube locations.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Ultimately, the risk of breast cancer remains at baseline and may limit the potential option for future HT if later developed 16 . Lastly, although the risk for ovarian epithelial cancer is considered reduced after risk-reducing bilateral salpingectomy, it still exists and could be lethal 17 …”
mentioning
confidence: 99%